Hydrogen energy storage integrated battery and supercapacitor based hybrid power system: A statistical analysis towards future research directions - Hannan M.A.; Abu S.M.; Al-Shetwi A.Q.; Mansor M.; Ansari M.N.M.; Muttaqi K.M.; Dong Z.Y. (Elsevier Ltd, 2023)
Hydrogen storage; Publishing; Secondary batteries; Statistical methods; Battery; Bibliometrics analysis; Cited papers; Future research directions; Hybrid power; Hybrid power system; Hydrogen cells; Hydrogen energy storages; Innovation research; Storage mechanism; Supercapacitor